Clock drawing test in Alzheimer disease screening - Oscanoa, Teodoro (2004)
OBJETIVE: To determine the value of the clock drawing test as a assessment tool for Alzheimer’s disease in elderly patients. MATERIAL AND METHODS: The clock drawing test was applied to patients with and without Alzheimer’s disease attended at the Almenara Hospital Geriatrics Department, Lima Perú. The sample consisted in 31 outpatients (10 males, 21 women) with Alzheimer’s disease and 31 outpatients without this disease (21 males, 10 women). They were requested to draw a clock, using standardized instructions (tenpoint clock drawing test ). Patient with Alzheimer’s disease were graded according to the Hughes’ Clinical Dementia Rating (mild in 10, moderate in 12 and severe in 9). RESULTS: Using a 6-point score as cut off the ten-point clock drawing test had a sensitivity of 83,9%, specificity of 93,5, positive predictive value of 92,9% and negative predictive value 83,5%. CONCLUSION: The ten-point clock test appears as a simple and effective test for the initial assessment of cognitive functions in elderly patients with suspected Alzheimer’s disease dementia.